The hemiplegic arm after stroke: measurement and recovery. - Wade, D T (1983)
Seven clinical tests have been used to study the recovery of arm function in 92 patients over 2 years following their stroke. These tests are simple and quick, and can be used by any interested observer. They form a hierarchical scale that measures recovery. Statistically significant improvement is only seen in the first 3 months. Fifty-six patients initially had non-functional arms; eight made a "complete recovery" and 14 a partial recovery. The tests described are inadequate on their own because they are not sufficiently sensitive at the upper range of ability. While recovery of lost function does relate to the degree of initial neurological loss in the arm, it seems to be largely independent of the overall severity of the stroke.